2016
DOI: 10.3390/nu8010031
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Sugars and Sugar-Sweetened Beverage Intake with Obesity in Korean Children and Adolescents

Abstract: Few studies have examined the association between dietary sugar intake and obesity in Asian children and adolescents. We evaluated the association of dietary sugar intake and its food source with obesity in Korean children and adolescents. In this cross-sectional analysis, data were obtained from five studies conducted between 2002 and 2011. The study included 2599 children and adolescents who had completed more than three days of dietary records and had anthropometric data. Total sugar intake was higher in gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 31 publications
(37 reference statements)
5
39
6
1
Order By: Relevance
“…This agrees with [6] [27] and [28] and disagrees with [20]. No significant association was found concerning other factors in agreement with [20] [22] and [29] as regards fast food and [29] and [30] as regards sugary juices. On the other hand, [6] [20] [23] and [28] disagree with us.…”
Section: Discussionsupporting
confidence: 87%
“…This agrees with [6] [27] and [28] and disagrees with [20]. No significant association was found concerning other factors in agreement with [20] [22] and [29] as regards fast food and [29] and [30] as regards sugary juices. On the other hand, [6] [20] [23] and [28] disagree with us.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies among children and adolescents have suggested an overall positive association of sugar-sweetened beverage consumption with obesity [41]. However, sugar intake from milk and fruits was inversely related to overweight and obesity in girls [42]. Sugar intake from different food sources might play an important role in the risk of obesity in children and adolescents [43].…”
Section: Risk Factors Of Obesity In Children and Adolescentsmentioning
confidence: 99%
“…With respect to the relationship between SSB consumption and socioeconomic status in general, it was found that SSB consumption was negatively correlated with socioeconomic status (Wold 2009, Mazarello Paes et al 2015. Nevertheless, in some countries, especially developing countries or countries in socioeconomic transition, a positive correlation was identified for SSB consumption and socioeconomic status (Han and Powell 2011, Ha et al 2016, Wold 2009). Such different patterns of the relationships among obesity, SSB consumption, and SES strongly support the need for further research on the effect of SSB tax in developing countries.…”
Section: Summary and Recommendationsmentioning
confidence: 99%